EFEKTIVITAS PENERAPAN PEMBELAJARAN INTERAKTIF BERBASIS MEDIA DONGENG DIGITAL TERHADAP LITERASI MEMBACA SISWA DI SD NEGERI 04 PALEMBANG - sri Sarbini; Magdad Hatim; Ida Suryani (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
The low reading literacy of elementary school students requires engaging and innovative learning, one of which is interactive learning based on digital storytelling media, a story-based medium that combines text, images, audio, and animation. This study aims to analyze the effectiveness of implementing interactive learning based on digital storytelling media on the reading literacy of second-grade students at SD Negeri 04 Palembang. The study employed a quantitative approach with a quasi-experimental method and a Pretest-Posttest non-equivalent control group design. The sample was determined through purposive sampling, consisting of 58 second-grade students from classes II A (experimental group) and II B (control group), with 29 students each. The research instrument was a validated 10-item multiple-choice reading literacy test. Data were analyzed using normality tests, homogeneity tests, and an independent sample t-test with IBM SPSS Statistics 25. The results showed that the experimental group's Posttest mean was 88.62, higher than the control group's 73.10, with a calculated t value of 5.018 > t table 2.003 and a significance of 0.000 < 0.05. These findings demonstrate that interactive learning based on digital storytelling media is effective in improving students' reading literacy, particularly in understanding explicit information, identifying key information, comprehending cause-and-effect relationships, and interpreting textual messages, making it a viable innovative alternative for reading instruction in elementary schools. ABSTRAK Rendahnya literasi membaca siswa sekolah dasar menuntut pembelajaran yang menarik dan inovatif, salah satunya melalui pembelajaran interaktif berbasis media dongeng digital, yaitu media cerita yang memadukan teks, gambar, audio, dan animasi. Penelitian ini bertujuan menganalisis efektivitas penerapan pembelajaran interaktif berbasis media dongeng digital terhadap literasi membaca siswa kelas II SD Negeri 04 Palembang. Penelitian menggunakan pendekatan kuantitatif dengan metode quasi experiment dan desain Pretest-Posttest non-equivalent control group design. Sampel penelitian ditentukan melalui purposive sampling, terdiri atas 58 siswa kelas II A (kelompok eksperimen) dan II B (kelompok kontrol), masing-masing 29 siswa. Instrumen penelitian berupa tes literasi membaca sebanyak 10 soal pilihan ganda yang telah divalidasi. Data dianalisis menggunakan uji normalitas, uji homogenitas, dan independent sample t-test dengan bantuan IBM SPSS Statistics 25. Hasil penelitian menunjukkan rata-rata Posttest kelompok eksperimen sebesar 88,62, lebih tinggi dibandingkan kelompok kontrol sebesar 73,10, dengan nilai t hitung 5,018 > t tabel 2,003 dan signifikansi 0,000 < 0,05. Temuan ini membuktikan bahwa pembelajaran interaktif berbasis media dongeng digital efektif meningkatkan literasi membaca siswa, khususnya dalam memahami informasi tersurat, menemukan informasi penting, memahami hubungan sebab-akibat, serta menafsirkan pesan bacaan, sehingga dapat menjadi alternatif inovatif pembelajaran membaca di sekolah dasar.